Properties of some higher-dimensional nonlinear Schrodinger equations - Nisar, Kottakkaran Sooppy; Inan, Ibrahim Enam; İnç, Mustafa; Rezazadeh, Hadi (Elsevier, 2021)
In this study, we have used the sub-equation method to provide some analytic solutions of the (2 + 1) and (3 + 1) dimensional nonlinear Schrodinger equations (NLSEs). We obtained are dark, bright and singular optical solitons. We observed through the Mathematica 11.2 program that these solutions provide the equations. Apart from that, we have shown the graphics performance of some of the solutions found. This method has been used recently to obtain exact traveling wave solutions of nonlinear partial differential equations.
Keywords: (2+1)-dimensional NLSE; (3+1)-dimensional NLSE; Sub-equation method; Optical soliton